2023
DOI: 10.3389/fpubh.2023.935292
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to the adoption of physical activity policies in elementary schools from the perspective of principals: An application of the consolidated framework for implementation research–A cross-sectional study

Abstract: BackgroundStudies have shown that policies to promote physical activity in schools can have a positive impact on children's physical activity behavior. However, a large research gap exists as to what determinants may influence the adoption of such policies. Applying the Consolidated Framework for Implementation Research (CFIR), we investigated barriers and facilitators to the adoption of physical activity policies in elementary schools in Baden-Wuerttemberg, Germany, from the perspective of school principals.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…While previous studies have identified PA preferences and barriers ( 17–19 ) among adolescents in schools, there is a lack of evidence on the habits and behaviors of inactive adolescents, particularly from the perspective of PE teachers. Although other school staff including headteachers/principals ( 20 ) have an impact, PE teachers are the gatekeepers for delivering interventions in schools and have a better understanding of the complex range of needs, attitudes, and preferences of inactive adolescents since they work with them every week.…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies have identified PA preferences and barriers ( 17–19 ) among adolescents in schools, there is a lack of evidence on the habits and behaviors of inactive adolescents, particularly from the perspective of PE teachers. Although other school staff including headteachers/principals ( 20 ) have an impact, PE teachers are the gatekeepers for delivering interventions in schools and have a better understanding of the complex range of needs, attitudes, and preferences of inactive adolescents since they work with them every week.…”
Section: Introductionmentioning
confidence: 99%
“…Between 2019 and 2022, seven reviews and three case studies were conducted to identify key requirements of policy implementation evaluation (see Supplementary Table ). Our experiences and findings of this research are summarized in case reports, including their objectives, methods, findings & lessons learned: case report 1: scoping reviews on implementation processes of sugar-sweetened beverage taxation and public physical activity policies [ 20 , 21 ] case report 2: a qualitative study on implementation determinants of the EU School Fruit and Vegetables Scheme [under review] case report 3: a meta-review on social, economic, political, and geographical context determinants for policies promoting a healthy diet and physical activity [ 22 ] case report 4: a systematic review of frameworks for implementation of policies promoting a healthy diet and physical activity [ 23 ] case report 5: a systematic review on acceptability of policies targeting dietary behaviours and physical activity [ 24 ] case report 6: meta-review of implementation determinants for policies promoting a healthy diet and physical activity [ 25 ] case report 7: a systematic review on implementation determinants of direct fruit and vegetables provision interventions in kindergartens and schools [ 26 ] case report 8: a quantitative cross-sectional study on determinants for the adoption of physical activity policies in elementary schools [ 27 ] case report 9: participatory stakeholder studies on implementation determinants following the Theory of Change approach [ 28 ] …”
Section: Methodsmentioning
confidence: 99%
“…case report 8: a quantitative cross-sectional study on determinants for the adoption of physical activity policies in elementary schools [ 27 ]…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the adoption of recycling practices in schools is influenced by various factors, and understanding stakeholders' perspectives, particularly principals, is crucial for policy implementation. The Consolidated Framework for Implementation Research (CFIR) is a valuable tool for interpreting study results and developing effective strategies in school settings, as highlighted by Wendt et al (2023). Studies have shown that education plays a crucial role in shaping individuals' awareness of waste management practices.…”
Section: Solid Waste Management Relative To Implementation Of Policie...mentioning
confidence: 99%